Microwave synthesis of novel water-soluble 2-, 5- and 9-substituted benzo[a]phenoxazinium chlorides in comparison with conventional heating - Firmino, A. D. G. (2013)
Microwave irradiation was used for the first time in an efficient synthesis of benzo[a]phenoxazinium chlorides. The main advantage of this protocol is the notable reduction in reaction times and good to excellent yields of the products were achieved in comparison with classical heating conditions as described. These new series of compounds possess 5-amine and/or 2-hydroxyl substituents in the polycyclic system to improve their solubility in aqueous media, in addition to the functional groups as terminals in the side chains, allowing their further use in covalent labeling. Fundamental photophysical studies carried out in ethanol, physiological pH and water revealed that all cationic fluorophores absorbed and emitted in the range of 610-628 nm and 630-652 nm, respectively, with relative fluorescent quantum yields ranging from 0.16 to 0.96.